Pemanfaatan Pupuk Organik Kotoran Kambing dan Abu Tandan Kosong Kelapa Sawit pada Pembibitan Awal Kelapa Sawit (Elaeis guineensis Jacq.) - Yuliyanto Yuliyanto; Rufinusta Sinuraya; Imam Sardian Pratama (JURNAL CITRA WIDYA EDUKASI, 2022)
This study aims to determine the effect of organic fertilizer application of goat manure and oil palm empty fruit bunch ash on the growth of oil palm seedlings and to obtain the best mixing of goat manure and oil palm empty fruit bunch ash for early seedling of oil palm. This study used a Randomized Block Design (RBD) method with 4 treatments, 3 replications and 2 samples. The treatment was carried out by adding a mixture of organic goat manure and oil palm empty fruit bunch ash in a ratio of 1:1 with different proportions on subsoil soil planting media. The research treatments were: P0 = No treatment (subsoil soil), P1 = subsoil soil + 100 grams of compost, P2 = subsoil soil + 150 grams of compost, P3 = subsoil soil + 200 grams of fertilizer. The results showed that organic fertilizer mixed with goat manure ash from empty fruit bunches of oil palm with a ratio of 1:1 can be used as an alternative to fertilization in early oil palm nurseries. The treatment had a significant effect on stem diameter in the third month and significantly affected weed growth.